2018
DOI: 10.20944/preprints201803.0110.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low-Dissipation Thermosets Derived from Oligo(2,6-dimethyl phenylene oxide)-containing Benzoxazines

Abstract: Poly(2,6-dimethyl phenyl oxide) (PPO) is known for its low dissipation factor. To achieve insulating materials with low dissipation factor for high-frequency communication application, a monomer-type benzoxazine (P-APPO) and a main-chain-type benzoxazine (BPA-APPO) were prepared from an amine end-capped oligo (2,6-dimethyl phenylene oxide) (APPO). The APPO was prepared from a nucleophilic substitution of a phenol-end capped oligo (2,6-dimethyl phenylene oxide) (a commercial product, SA 90) with fluoronitrobenz… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Very recently, Lin reported that poly(2,6-dimethylphenyl oxide) (PPO) containing benzoxazine resin could reach the high-frequency requirement of f value below 0.005 (1 GHz), due to the main component of thermoplastic PPO. 6 In this paper, we first report, to the best our knowledge, the pure thermosetting benzoxazine resins owning low k (<3) and ultralow f (<0.005) values under high frequencies (5 and 10 GHz).…”
mentioning
confidence: 97%
“…Very recently, Lin reported that poly(2,6-dimethylphenyl oxide) (PPO) containing benzoxazine resin could reach the high-frequency requirement of f value below 0.005 (1 GHz), due to the main component of thermoplastic PPO. 6 In this paper, we first report, to the best our knowledge, the pure thermosetting benzoxazine resins owning low k (<3) and ultralow f (<0.005) values under high frequencies (5 and 10 GHz).…”
mentioning
confidence: 97%